Manajemen Pembelajaran di MIS Hidayatul Insan Palangka Raya - Muhammad Tri Ramdhani; Istiqlaliyah Istiqlaliyah (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Learning management can be interpreted as an effort to manage the resources used in learning so that the learning objectives can be achieved effectively and efficiently. Selection of appropriate learning model will determine the interest, participation of learners, and will minimize the problems faced by teachers in learning. In the field of learning is expected teachers can manage to learn by determining the appropriate learning model so as to attract learners' interest in the subject matter. The learning management at MIS Hidayatul Insan Palangkaraya includes preparation, implementation, and evaluation. Problems faced by teachers in MIS Hidayatul Insan Palangkaraya, the problem of how to instill the same concept in learners. One way teachers overcome this is to provide an easy example so that learners can understand. After doing some preparation and carrying out the learning the teacher performs the evaluation assigning the task to the learners.